Successful Postnatal Management of Ruptured Giant Sacrococcygeal Teratoma - Muataz Abdulhameed Al ani (EL-Med-Pub, 2017)
Most sacrococcygeal teratomas present between the 22nd and the 34th week of gestation. The diagnosis of sacrococcygeal teratoma on routine antenatal sonograms is associated with a greater than expected incidence of prenatal and perinatal complications. We report a premature baby with intrauterine spontaneous rupture of giant sacrococcygeal teratoma which was managed successfully.